Transmission Wheeling Pricing in Embedded Cost Using Modified Amp-Mile and MVA Utility Factor Methods - Jain, Gaurav; Palwalia, Dheeraj Kumar; Mishra, Anuprita (Advances in Technology Innovation, 2019)
Transmission wheeling pricing is one of the decisive aspects of present open access electricity market. Various methods are available for transmission; however, no method is proved to diverse operating conditions of power system. These methods are not able to quantify the full recovery of embedded cost. All the variables i.e. remaining charges, used circuit capacity are not counted in the existing methods. This Paper explicates two methods, Modified Amp – Mile method and MVA Utility Factor method, to recover embedded cost. Modified Amp-Mile method is customized form of existing Amp-Mile method. In the MVA Utility Factor method, cost allocation is based on marginal participation (MP). It evaluates the cost, using sensitivity analysis of network power. The proposed methods are tested on an IEEE 6 bus system and further verified on Hadoti region real 37 bus system. All the results are presented in Full Recovery Model (FRM) and Partial Recovery Model (PRM).